SAT0512 Comparison of Asdas ESR/ASDAS CRP with Basdai and Clinical Disease Activity in Enthesitis Related Arthritis. (9th June 2015) - Agarwal, M.; Sawhney, S.
Abstract : Background: BASDAI is a disease assessment tool that entirely depends upon patient/parent reporting and may not be able to capture the disease status when compared to clinical judgement. The cutoff range for high disease activity is 3.9 and those below this level though active do not fit into any group.Children often tend to overreport or under report and a more objective disease activity tool is warranted.ASDAS ESR and ASDAS CRP have been studied in adults but no such data in children from our country was available. Thus we intended to look for a more objective disease assessment tool for children with Enthesitis Related Arthritis and hence this pilot study was undertaken Objectives: 1.) compare BASDAI with ASDAS ESR and ASDAS CRP 2.) To compare disease activity status clinically and with ASDAS ESR and ASDAS CRP Methods: 200 consecutive BASDAI was collected on paper forms from all children diagnosed as Enthesitis related arthritis by ILAR classification who attended the pediatric rheumatology clinic.Patient global score and physician global scores were given and ASDAS ESR, ASDAS CRP were calculated using the ASDAS calculator available online Results: 200 BASDAI forms were collected from 110 children (87 boys). At disease onset, 10 children had only axial involvement and 44 children had only peripheral disease whereas 53 had both axial and peripheral involvement. Only 7.5% were more than 3.9 indicating very high disease activity warranting a biologic agent. ASDAS ESR was able to pick up all those with high disease activity on BASDAI. A high level of agreement was found in ADAS ESR and disease status clinically. ASDAS CRP picked up all with high disease activity on BASDAI Conclusions: ASDAS ESR and ASDAS CRP were both able to correlate well with clinical disease activity.CRP rises earlieras compared to ESR and falls more rapidly and is mirrored with more children with clinically inactive disease with low disease activity by ASDAS CRP as compared to ASDAS ESR. Limitations: Change of ASDAS ESR and ASDAS CRP over time has not been studied Disclosure of Interest: None declared